Magnitude of risky sexual behaviors, determinants, and consequences among high school and preparatory school students in Mizan Aman Town, Ethiopia - Tadesse Nigussie; Tegene Legesse; Lemi Abebe; Selamawit Getachew; Dereje Alemayehu (Mashhad University of Medical Sciences, 2020)
Background & aim: Adolescence is the period when young people learn about sexual activity. This period exposes them to different challenges if not properly managed. Therefore, the present study aimed to determine the prevalence of risky sexual behaviors as well as its associated factors and consequences among high school and preparatory school students. Methods: This facility-based cross-sectional study was carried out among 349 randomly selected high school and preparatory students of Mizan Aman Town, Ethiopia, during May, 2018. For data collection a structured and validated questionnaire regarding risky sexual behaviors was filled out by students. The data were analyzed using SPSS software (version 21). Logistic regression with 95% confidence interval (CI) was used to determine independent factors, and p-value less than 0.05 in multivariable logistic regression was used to demonstrate statistical significance. Results: The prevalence rate of risky sexual behaviors was reported as 30.5%. Risky sexual behaviors were associated with issues including being from rural areas (AOR=2.041; 95% CI: 1.224-3.403), watching pornography (AOR=2.142; 95% CI: 1.219-3.766), and discussing the issue of sexuality with family (AOR=0.349; 95% CI: 0.191-0.541). Regarding the consequences of risky sexual behaviors, 8% of the respondents reported a history of signs or symptoms related to sexually transmitted infections (STIs), and 7.05% of the females had a history of an unplanned pregnancy. Conclusion: One-third of the study participants had risky sexual behaviors. The residents of rural areas and students who watched pornographic films were at a higher risk and the participants who had a discussion about sexuality with their families were at a lower risk of risky sexual behaviors. The STIs, unplanned pregnancy, and abortion were the consequences of risky sexual behaviors.